2009
DOI: 10.1165/rcmb.2008-0155oc
|View full text |Cite
|
Sign up to set email alerts
|

Azithromycin Reduces Exaggerated Cytokine Production by M1 Alveolar Macrophages in Cystic Fibrosis

Abstract: Macrophages phagocyte pathogenic microorganisms and orchestrate immune responses by producing a variety of inflammatory mediators. The cystic fibrosis (CF) transmembrane conductance regulator chloride channel has been reported to be of pivotal importance for macrophage functions. The exact phenotype and role of macrophages in CF is still unknown. Alveolar and peritoneal macrophages were monitored in CF mice homozygous for the F508 del mutation and in wild-type control animals. Classical (M1) and alternative (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
100
3
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(117 citation statements)
references
References 53 publications
11
100
3
3
Order By: Relevance
“…However, as other cells such as neutrophils and alveolar macrophages play a pivotal role in CF airway disease pathogenesis, we cannot exclude a bronchial epithelial cell-independent role of azithromycin, especially in the context of possible anti-inflammatory properties of azithromycin. Indeed, a recent study shows that azithromycin reduces the pro-inflammatory cytokine production of M1-polarised alveolar macrophages in CF mice [41], and decreases pro-inflammatory cytokines expression such as IL-8 or tumour necrosis factor-α by human alveolar macrophages of CF [42] and healthy subjects [43]. Furthermore, macrolides have been shown to reduce the activation of neutrophils and to decrease neutrophil chemotaxis to the site of infection in the airways [44].…”
Section: Discussionmentioning
confidence: 99%
“…However, as other cells such as neutrophils and alveolar macrophages play a pivotal role in CF airway disease pathogenesis, we cannot exclude a bronchial epithelial cell-independent role of azithromycin, especially in the context of possible anti-inflammatory properties of azithromycin. Indeed, a recent study shows that azithromycin reduces the pro-inflammatory cytokine production of M1-polarised alveolar macrophages in CF mice [41], and decreases pro-inflammatory cytokines expression such as IL-8 or tumour necrosis factor-α by human alveolar macrophages of CF [42] and healthy subjects [43]. Furthermore, macrolides have been shown to reduce the activation of neutrophils and to decrease neutrophil chemotaxis to the site of infection in the airways [44].…”
Section: Discussionmentioning
confidence: 99%
“…For example, Kent et al (11) produced a congenic Cftr tm1UNC mouse strain in C57BL/6J (B6) background and showed the lung disease measured in these mice to include clinical attributes such as a perpetual neutrophil influx (12)(13)(14), patchy inflammation (15), mucus accumulation, and interstitial fibrosis in the lower airways (1). Altered macrophage function (16) and increased numbers of neutrophils in the bronchoalveolar lavage of Cftr tm1Eur mice (17) and subepithelial accumulation of lymphocytes in nasal tissue of Cftr tm1UNC and Cftr TgHm1G551D mice have also been reported (18). Finally, our study using microarrays to molecularly assess the lung phenotype of Cftr tm1UNC mice in each of the C57BL/6J and BALB/cJ (BALB) genetic backgrounds revealed T and B cell proliferation to be among the biologic processes prominent in the BALB Cftr tm1UNC mice (19).…”
Section: mentioning
confidence: 99%
“…LPS challenge led to substantial induction of M1 signature genes in CF mice than in wild-type mice indicating that bacterial infection on a background of intrinsic CFTR mutation worsen the pulmonary inflammation. On the contrary, polarization of M2 signature genes as well as IL-10, hallmark M2 soluble marker in mouse, were not remarkably induced in AMs and PMs of CF mice (257). Taken together, this data suggests exaggerated pro-inflammatory responses in CF with basal or no induction of anti-inflammatory M2 macrophages.…”
Section: Macrophages: the Missing Link In Cf Inflammation?mentioning
confidence: 66%
“…Studies showed spontaneous infiltration of monocytes and macrophages in alveolar spaces as well as local tissues, such as, peritoneum (257). Depending on the post translational processing, three isoforms of CFTR proteins have been shown in earlier studies (176) human macrophages (160).…”
Section: Macrophages: the Missing Link In Cf Inflammation?mentioning
confidence: 92%
See 1 more Smart Citation